An Appraisal of the Perception of the Continuous Assessment Practice among Primary School Teachers in Ogun State - Adetayo, Janet Oyebola (NIU Journal of Humanities, 2018)
The study sought to examine primary school teachersâ€™ perception of the Continuous Assessment practice in Ogun State.  Four research questions were raised, the sample for the study consists two hundred (200) teachers who were randomly selected from the four geopolitical zones in Ogun State.  A questionnaire was the only instruments used for data collection.  Data collected were analyzed descriptively and inferentially using t-test of significance at 0.05 level of confidence.  The result of the findings reveals that primary school teachers have high perception about continuous assessment practice. There is no significant difference between male and female teachersâ€™ perception of the continuous assessment practice, there is a significant difference between young and old teachers while there is no significant difference between the perception of continuous assessment practices among public and private school teachers.  Based on these findings, it was concluded that continuous assessment practices was poor and the implementation of continuous assessment is bedeviled with several difficulties.  Therefore, recommendations were made that ministry of education should establish a uniform standard of assessment, and a uniform system of weighting scores from different assessments should be used from school to school. Keywords: Appraisal, Perception, Continuous Assessment, Primary school Teachers.